Case Report: VEXAS Syndrome: From Mild Symptoms to Life-Threatening Macrophage Activation Syndrome - Staels, Frederik; Betrains, Albrecht; Woei-A-Jin, F. J. Sherida H.; Boeckx, Nancy; Beckers, Marielle; Bervoets, An; Willemsen, Mathijs; Neerinckx, Barbara; Humblet-Baron, Stephanie; Blockmans, Daniel Engelbert; Vanderschueren, Steven; Schrijvers, Rik (Frontiers in Immunology, 2021)
Recently, a novel disorder coined VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome was identified in patients with adult-onset inflammatory syndromes, often accompanied by myelodysplastic syndrome. All patients had myeloid lineage-restricted somatic mutations in UBA1 affecting the Met41 residue of the protein and resulting in decreased cellular ubiquitylation activity and hyperinflammation. We here describe the clinical disease course of two VEXAS syndrome patients with somatic UBA1 mutations of which one with a mild phenotype characterized by recurrent rash and symmetric polyarthritis, and another who was initially diagnosed with idiopathic multicentric Castleman disease and developed macrophage activation syndrome as a complication of the VEXAS syndrome. The latter patients was treated with anti-IL6 therapy (siltuximab) leading to a resolution of systemic symptoms and reduction of transfusion requirements.